On the Edge of Space and Time: Evangelical Missionaries in the Post-Soviet Arctic - Laur Vallikivi (Journal of Ethnology and Folkloristics)
Evangelical missionaries have missionised pretty much throughout Russia after the collapse of the Soviet Union. Among their favourite targets are the small-numbered indigenous groups in the Russian Arctic, where the numbers of converts are steadily growing. One particular denomination, known as the Unregistered Baptists, are among the leading agents of religious change in the North today. They are driven by the promise of the return of Christ after the gospel is preached “at the ends of the earth”. I suggest that the Baptists’ agenda is shaped, on the one hand, by the literal reading of the Bible, which allows them to be the divine instruments at the end times and, on the other hand, by the idea of Russia’s special role in God’s salvation plan. I shall analyse the Baptists’ ideas and practices, using among others Bakhtin’s concept of chronotope in order to demonstrate how powerful narratives are created and lived.